Busting the Boom–Bust Pattern of Development in the Brazilian Amazon. (March 2016) - Caviglia-Harris, Jill; Sills, Erin; Bell, Andrew; Harris, Daniel; Mullan, Katrina; Roberts, Dar
Summary: Global ecosystem services are clearly threatened by deforestation associated with human occupation and economic development of the Brazilian Amazon. However, the prognosis for the socioeconomic wellbeing of inhabitants remains unclear. In an empirical regularity that has been termed the boom–bust pattern or the resource curse, the exploitation of natural resources is associated with short-run gains in welfare that dissipate over time. This "coupling hypothesis" asserts that deforestation and development are correlated such that deforestation leads to only short-term advances in economic welfare that are not sustained once natural forests (along with their mature timber and soil inputs) are exhausted. In contrast, the "decoupling hypothesis" asserts that deforestation and development need not be correlated over time. In this context, growth that is initially based on deforestation may be sustained and translated into prolonged welfare gains, even once the forest is exhausted. Using census and deforestation data from 1991, 2000 and 2010 for municipalities (i.e., counties) in the Amazon region we confirm that this boom–bust pattern appears in cross-sectional data. However, using panel data we show that socioeconomic welfare has become decoupled from environmental factors and is converging to rising national averages. Our findings contradict the conventional wisdom that the exploitation of tropical forests is required to promote Amazonian development.